Coordinated cellular and humoral immune responses after two‐dose SARS‐CoV2 mRNA vaccination in liver transplant recipients. (17th November 2021) - D'Offizi, Gianpiero; Agrati, Chiara; Visco‐Comandini, Ubaldo; Castilletti, Concetta; Puro, Vincenzo; Piccolo, Paola; Montalbano, Marzia; Meschi, Silvia; Tartaglia, Eleonora; Sorace, Chiara; Leone, Sara; Lapa, Daniele; et al.
Abstract: Limited data are available on risks and benefits of anti‐SARS‐CoV2 vaccination in solid organ transplant recipients, and weaker responses have been described. At the Italian National Institute for Infectious Diseases, 61 liver transplant recipients underwent testing to describe the dynamics of humoral and cell‐mediated immune response after two doses of anti‐SARS‐CoV2 mRNA vaccines and compared with 51 healthy controls. Humoral response was measured by quantifying both anti‐spike and neutralizing antibodies; cell‐mediated response was measured by PBMC proliferation assay with IFN‐γ and IL‐2 production. Liver transplant recipients showed lower response rates compared with controls in both humoral and cellular arms; shorter time since transplantation and multi‐drug immunosuppressive regimen containing mycophenolate mofetil were predictive of reduced response to vaccination. Specific antibody and cytokine production, though reduced, were highly correlated in transplant recipients.